More than half of China's CO2 emissions are from micro, small and medium-sized enterprises. (15th November 2018) - Meng, Bo; Liu, Yu; Andrew, Robbie; Zhou, Meifang; Hubacek, Klaus; Xue, Jinjun; Peters, Glen; Gao, Yuning
Highlights: Firm size and ownership information is crucial in analyzing China's carbon emissions. MSMEs produced 53%, induced 65% of China's CO2 emissions along domestic supply chains. Private MSMEs in the non-metallic mineral sector should be the key for policy-making. Given the abundance of MSMEs, taxation is suitable for further emissions reduction. Reducing environmental externalities in China need more supply-chain based governance. Abstract: To date, the burden of CO2 emissions reductions has been largely confined to large enterprises in China. Using new data with firm ownership and size information included, we show that micro, small and medium-sized enterprises (MSMEs) produced 53% of China's CO2 emissions in 2010. Detailed supply-chain analysis reveals that final demand for products made downstream by domestic-private MSMEs, along with exports made downstream by foreign-owned MSMEs, are the main drivers of China's CO2 emissions. Most of these emissions occur upstream in the electricity and heat sector, which is mainly controlled by large, state-owned enterprises with the highest carbon intensity, and the non-metallic mineral sector, which consists of a very large number of domestic-private MSMEs with lower levels of enforcement of emissions regulations. Overall, MSMEs induced 65% of China's CO2 emissions through their supply chains. Our conclusion is that understanding the role of firm size for China is important in developing emissions reduction policies: given the very high per-enterprise overhead of emissions trading systems, and the abundance of MSMEs, our results clearly favour taxation.